Między pamięcią a łagodzeniem traumy. Rzeź wołyńska w wierszach Wojciecha Wencla z tomu "De profundis" i w opowiadaniach Stanisława Srokowskiego z cyklów "Nienawiść" i "Strach" = Between the memory and the assuagement of trauma. Volhynian massacre in the poems by Wojciech Wencel from the collection "De profundis" and in the short stories by Stanisław Srokowski from the cycles "Nienawiść" and "Strach" - Kulczycka, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Author raises the following subject: how the authors, mentioned in the title, balance between the inner command to tell the truth about the borderland events from the time of World War II and the neutralisation of the undesired feelings, which might be evoked by this truth in the readers.
Keywords: Massacres of Poles in Volhynia and Eastern Galicia; poetry; stories; memory; trauma; Srokowski, Stanisław (1936- ); Wencel, Wojciech (1972- ); pamięć; poezja; Wołyń; Galicja